R&D spillovers and total factor productivity in South Korea with ARDL approach - Ibrahim, Saifuzzaman; Mohd Sidek, Hazirah; Wan Ngah, Wan Azman Saini; Abdul Rahman, Mazlina (Transition Academia Press, 2014)
This study aims to examine the impact of R&D spillovers on the South Korean total factor productivity (TFP) using the Autoregressive Distributed Lag (ARDL) estimation technique. Using data from the period 1985-2005, the results show that the domestic research and development (R&D) expenditure and foreign direct investment (FDI) have positive im- pact on the productivity growth in South Korea, in the long run. However, in the short run, the domestic R&D and the imports of goods and services have significant positive impact on the country’s TFP.